THE RELATIONSHIP AMONGST SOEHARTO, MILITARY, AND MUSLIM IN THE END OF NEW ORDER REGIME - Fatgehipon, Abdul Haris (History Department, Semarang State University and Historian Society of Indonesia, 2016)
In the end of Suharto's authority, he began to embrace the power of Islam; he realized the position of Muslims was very important and strategic. While some high-ranking military, like LB Moerdani felt unhappy with business built by Soehartoâ€™s family. Suharto built a new political power through the ICMI (Indonesian Muslim Scholar) organization. The emergence of ICMI has been confronted by much of the military officers, they assessed that ICMI shaped sectarian mindset, Gus Dur as NU leader also did not approve the establishment of ICMI. ICMI was chaired by BJ Habibie who at that time had a special affinity with Suharto that made ICMI has the most important role in Indonesian and clout. At the end of Suharto's power, he embraced the power of the Muslim Civilians, Reviews such as ICMI and Muhammadiyah organization. He tried to minimize the political dependence on the military. Hereinafter, Habibie has successfully elected as a vice president of Indonesia based on the general assembly in 1998, after the riots in May 1998, Habibie replaced Suharto's position that has discharged due to students and citizens' demonstrations. By the pretense of the 1945 constitution, the military endorsed the nomination of BJ Habibie as president.Â Pada akhir otoritas Soeharto, ia mulai merangkul kekuatan Islam; ia menyadari posisi Muslim sangat penting dan strategis. Sementara beberapa petinggi militer, seperti LB Moerdani merasa tidak bahagia dengan bisnis gurita yang dibangun oleh keluarga Soeharto. Soeharto membangun kekuatan politik baru melalui organisasi ICMI (Indonesian Muslim Scholar). Munculnya ICMI telah dihadapkan oleh banyak perwira militer, mereka menilai ICMI berbentuk pola pikir sektarian, Gus Dur sebagai pemimpin NU juga tidak menyetujui berdirinya ICMI. ICMI dipimpin oleh BJ Habibie yang pada waktu itu me-miliki kedekatan khusus dengan Soeharto yang membuat ICMI memiliki peran paling penting dalam Indonesia dan pengaruh. Pada akhir kekuasaan Soeharto, ia memeluk kekuatan Sipil Muslim, Ulasan seperti ICMI dan Muhammadiyah organisasi. Dia mencoba untuk meminimalkan ketergantungan politik pada militer. Selanjutnya, Habibie telah berhasil terpilih sebagai wakil presiden Indonesia berdasarkan sidang umum pada tahun 1998, setelah kerusuhan Mei 1998, Habibie menggantikan posisi Soeharto yang telah habis karena mahasiswa dan de-monstrasi warga. Dengan berdasar UUD 1945, militer mendukung pencalonan BJ Habibie sebagai presiden.Â